1996
DOI: 10.1074/jbc.271.20.11810
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Active-site Residues in Saccharomyces cerevisiae Ferrochelatase by Directed Mutagenesis

Abstract: Ferrochelatase is a mitochondrial inner membranebound enzyme that catalyzes the insertion of ferrous iron into protoporphyrin, the terminal step in protoheme biosynthesis. The functional/structural roles of 10 invariant amino acid residues were investigated by sitedirected mutagenesis in the yeast Saccharomyces cerevisiae ferrochelatase. The mutant enzymes were expressed in a yeast strain lacking the ferrochelatase gene HEM15 and in Escherichia coli. The kinetic parameters of the mutant enzymes were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 37 publications
6
55
0
Order By: Relevance
“…Although the iron substrate ligands in ferrochelatase remain to be unequivocally identified, nitrogenous and/or oxygenous ligands appear to coordinate the metal substrate (32,42,43 (13). Thus, an increase in the K m Fe 2ϩ of the triple mutant S249A/K250Q/V251C may account for the loss of the stabilization provided by Ser 249 (Table I).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the iron substrate ligands in ferrochelatase remain to be unequivocally identified, nitrogenous and/or oxygenous ligands appear to coordinate the metal substrate (32,42,43 (13). Thus, an increase in the K m Fe 2ϩ of the triple mutant S249A/K250Q/V251C may account for the loss of the stabilization provided by Ser 249 (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…3). In addition, mutation of the corresponding residue in yeast ferrochelatase (Trp 282 ) yielded a variant (W282L) exhibiting a 10-fold decrease in K m PPIX and an unaltered K m for the metal substrate (32). Actually, the homologous residue in B. subtilis ferrochelatase (Trp 230 ) was shown to stack against the pyrrole ring, thereby stabilizing the position of the porphyrin ring in the crystal structure (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…extended X-ray absorption fine structure and Mössbauer), X-ray crystallography and site-directed mutagenesis have been used to characterize the metal-binding sites of ferrochelatase [5,[29][30][31][32][33][34][35]. Mössbauer and X-ray absorption spectroscopies have indicated that ferrochelatase has an ionic coordination environment for Fe 2+ with six nitrogen-and/or oxygen-containing ligands [29,30].…”
Section: Metal Ion Binding and Shuttlingmentioning
confidence: 99%
“…Among these residues are a histidine (H183 in B. subtilis ferrochelatase and H207 in the murine mature enzyme) and a glutamate (E264 in B. subtilis ferrochelatase and E287 in the murine mature enzyme). The active site histidine and glutamate have been advocated to be involved in metal substrate binding(l2, 13) and in catalysis (14), respectively. Biophysical characterization of human and mouse ferrochelatase has shown that these enzymes contain a [2Fe-2S] cluster (15,16).…”
Section: Introductionmentioning
confidence: 99%